Nutritional risk is associated with an increase of in-hospital mortality and a reduction of being discharged home: Results of the 2009–2015 nutritionDay survey. (August 2020) - Cardenas, Diana; Bermúdez, Charles; Pérez, Angélica; Diaz, Gustavo; Cortes, Lilia Yadira; Contreras, Claudia Patricia; Pinzón-Espitia, Olga Lucía; Gomez, Gabriel; Gonzalez, Maria Cristina; Fantin, Romain; Gutierrez, José; Sulz, Isabella; et al.
Summary: Background: Disease-related malnutrition is a known factor for poor outcomes. However, there is a lack of knowledge about the prevalence and the impact of nutritional risk on outcomes in Colombia. The aim of the present study was to determine the prevalence of nutritional risk, to know how nutrition screening is routinely performed and to determine the impact of nutritional risk on the outcomes of in-hospital mortality and being discharged home outcomes. Methods: We conducted a descriptive analysis of selected data from 7 consecutive, annual, and cross-sectional nutritionDay samples (2009–2015) including a total of 7, 994 adult patients in 248 units in Colombia. Data is contrasted with the Latin American and worldwide results. The prevalence of nutritional risk was determined according to the malnutrition screening tool (MST). The impact of nutritional risk in Colombian patients regarding outcomes was assessed by a Fine and Gray competing risk regression model controlling for PANDORA score (age, BMI, length of stay before nutritionDay, cancer diagnosis, and mobility). Results: The prevalence of nutritional risk (MST score ≥ 2) in Colombia was 38%, 41% in Latin America, and 32% worldwide. Half of the Colombian units screened patients for malnutrition or nutritional risk on admission to hospital, compared to 80% in Latin America and 62% worldwide. Only 23% of the Colombian patients identified as being at nutritional risk in the nutritionDay survey received any nutritional therapy. The hospital mortality hazard ratio of Colombian patients at nutritional risk defined by MST was 1.94 (95% CI, 1.53, 2.46; p < 0.001) and 0.82 of being discharged home (95% CI, 0.76, 0.88, p < 0.001). Conclusions: This is the first large-scale study in Colombia evaluating the impact of nutritional risk on clinical outcomes showing an increase of in-hospital mortality and a reduction of being discharged home. Moreover, the study shows that nutritional risk is still highly prevalent worldwide implying the need to promote an optimal nutritional care. The participation of Latin American countries in the nutritionDay survey is an opportunity to increase knowledge and awareness of these issues.